The Role of Direct Marketing Policies in Achieving Customer Satisfaction: An Eploratory Study of a Sample of Commercial Companies in The City of Sulaymaniyah - ويس مراد, سه روه ت روستم; حمه صالح, سوران حمه سعيد; مجيد, ڕەوەند محمد; علي, زريان جبار رؤوف (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The research aims to know the role of direct marketing policies in achieving customer satisfaction in a group of commercial companies in the city of Sulaymanyah. Likert quintuple scale, and to identify the respondents' opinions, the questionnaire was submitted electronically to workers in the commercial companies in question, and (216) responses were obtained, and a number of statistical tools and methods were used to test the hypotheses of the study through the (SPSS. To a set of conclusions, including: the existence of a correlation relationship and a significant effect between the dimensions of direct marketing (direct mail - direct selling, e-marketing via the Internet) and achieving customer satisfaction, while the effect was not achieved for the dimension of telemarketing, and a set of recommendations were presented, the most important of which is the need to pay attention to electronic promotion In general, and especially when providing new services by placing advertisements on social networking sites, and trying to communicate with customers through Communication face to face through delegates. Keywords: direct marketing, customer satisfaction, commercial companies, the city of Sulaymaniyah.